Analyzing the Interaction between R&D Subsidies and Firm’s Innovation Strategy - Sergio Moises Afcha (Journal of Technology Management & Innovation, 2012)
Innovation and Technology policies provide positive incentives to the firms to perform R&D activities. This article examines the decision of internal and external R&D expenditures of subsidized firms, estimating the impact of R&D subsidies on firms performing different innovation strategies. The Spanish survey on business strategy for manufacturing firms (ESEE) is used for the period 1998-2005. Results show that determinants of pure internal or external R&D expenditures obey to different motivations, affecting in consequence, the impact of the subsidies on firms adopting different sources of knowledge.